Burden, Etiology, and Risk Factors of Respiratory Virus Infections Among Symptomatic Preterm Infants in the Tropics: A Retrospective Single-Center Cohort Study. (12th April 2018) - Yeo, Kee Thai; de la Puerta, Rowena; Tee, Nancy Wen Sim; Thoon, Koh Cheng; Rajadurai, Victor S; Yung, Chee Fu
Abstract : This study describes the burden of respiratory virus infections (RVIs) among preterm infants in the tropics. RVIs affected >1 of 10 infants born at ≤32 weeks' gestation before age 2 years, with respiratory syncytial virus being the main causative pathogen. Abstract: Background: The burden of respiratory viral infections (RVIs) among preterm infants in the first few years of life, especially those living in the tropics with year-long transmissions of respiratory viruses, remains unknown. We aimed to describe the clinical epidemiology and associated risk factors for RVIs among symptomatic preterm infants ≤32 weeks up to 2 years of life. Methods: We performed a data linkage analysis of clinical and hospital laboratory databases for preterm infants born at KK Women's and Children's Hospital, Singapore, from 2005 to 2015. RVI episodes during initial admission and subsequent hospital readmissions were included. Results: Of 1854 infants in the study, 270 (14.5%) infants were diagnosed with at least 1 RVI. A total of 285 (85.3%) episodes were diagnosed postdischarge, with the highest risk for RVIs being from 3 to 5 months of age. The incidence of RVI in this population was 116 per 1000 infant-years and respiratory syncytial virus was the main overall causative pathogen. Infants with RVIs were more likely to be born at ≤27 weeks' gestational age (odds ratio [OR], 1.7; 95% confidence interval [CI], 1.2–2.3), to have received postnatal steroids (OR, 1.5; 95% CI, 1.0–2.1), and to be diagnosed with bronchopulmonary dysplasia (OR, 1.7; 95% CI, 1.2–2.4). Conclusions: The burden of RVIs is high in preterm infants in the tropics, affecting >1 of 10 infants born at ≤32 weeks' gestation before 2 years of age. Respiratory syncytial virus was the main causative pathogen identified. Risk factors for RVI included extremely low gestational age, receipt of postnatal steroids, and bronchopulmonary dysplasia.